An historical analysis of multifaith cooperation and civilisation building in India during Muslim rule - Arshad, Islam, Arshad Islam (2017)
India has always been a multi-cultural, multi-racial and multi-religious melting pot of diverse civilizations since ancient times, readily absorbing diverse beliefs, customs, religions and philosophies, not viewing them as existential ‘problems’ like modern nations but rather glorying in the everlasting unity of the diverse elements that comprise India’s multifarious and eclectic beauty. Islam was the third major cultural development in India (after Hinduism and Buddhism), initially arriving with Arab trading communities around the coastal ports and later with the Muslim conquest of Sind, which set the scene for successive Islamic polities throughout India, whereby foreign and indigenous Muslim rulers adapted the ethics and laws of Islam to the welfare of their subjects, granting minorities (and Hindu-Buddhist majorities in many cases) the freedom to practice their religions, which enriched religious, cultural and scientific life in the Subcontinent and led to a massive Indian contribution to Islam itself. This paper sheds light on the attitudes and policies of Muslim rulers in their engagement with the diverse religious groups in the country and examines the challenges in the execution of multifaith cooperation in building a harmonious and sustainable civilization based on equality and justice. Multifiath relationships embody the notion of mutual understanding and respect for the beliefs and practices of others. In the modern globalised world with its increasing political and economic dissension, peaceful coexistence among peoples of different religious beliefs can prove to be the way forward for peace and prosperity and became a role model for contemporary world. The glorious past of Indian multifaith cooperation under historical Muslim governments is a glittering example of the potential of genuinely inclusive cultural and religious cooperation, as manifest in the unique Ganga-Jamuni Tehzib (Ganges-Jamuna culture), a synergy of Hindu-Muslim cultural elements that flourishes in the regions of Awadh and southern India.